1951
DOI: 10.1113/expphysiol.1951.sp000963
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vasomotor Responses of Isolated Perfused Cat Lungs to Anoxia and Hypercapnia

Abstract: RECENT observations in the intact animal indicate that a decrease in 02 concentration in the inspired air may act, as does CO2, on the pulmonary vessels to produce constriction [for references see Duke, 1949 a; Dirken and Heemstra, 1949 a, b, c; Nisell, 1950]. Isolated perfused lungs provide a means of determining whether these effects are independent of neuro-humoral reflexes. When this investigation was begun, Lohr [1924] had used this technique to study pulmonary vasomotor responses of the cat in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

1952
1952
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 2 publications
2
33
0
Order By: Relevance
“…It is therefore possible that the additional increase in pulmonary vascular conductance which was seen when the lungs 203 204 G. V. R. BORN, G. S. DAWES AND JOAN C. MOTT were ventilated with air, after ventilation with nitrogen, may have been due to the removal of vasoconstrictor substances formed in the absence of sufficient oxygen. Alternatively the phenomenon may be related to that observed by Nisell (1948Nisell ( , 1950 and Duke (1951Duke ( , 1954 in the isolated perfused lungs of cats and ascribed to changes in the oxygen tension of the alveolar air or the perfusate.…”
Section: *Tripletsmentioning
confidence: 99%
“…It is therefore possible that the additional increase in pulmonary vascular conductance which was seen when the lungs 203 204 G. V. R. BORN, G. S. DAWES AND JOAN C. MOTT were ventilated with air, after ventilation with nitrogen, may have been due to the removal of vasoconstrictor substances formed in the absence of sufficient oxygen. Alternatively the phenomenon may be related to that observed by Nisell (1948Nisell ( , 1950 and Duke (1951Duke ( , 1954 in the isolated perfused lungs of cats and ascribed to changes in the oxygen tension of the alveolar air or the perfusate.…”
Section: *Tripletsmentioning
confidence: 99%
“…5 of the 15 patients had increases in flow that exceeded 0.48 liter per minute per square meter of body surface; this value had been previously calculated in this laboratory as representing the limit of variation that might, with 95 per cent confidence, be anticipated to occur between successive Fick measurements.9 These patients (E.C., P.G., W.B., B.S., and J.S.) also had the largest increases in oxygen uptake, ranging from 11 to 30 per cent; indeed, the largest increment in flow of +41 per cent occurred in patient J.S., who showed the largest increment in oxygen uptake (+30 per cent).…”
Section: Arterial Blood Oxyhemoglobin Saturationmentioning
confidence: 99%
“…Possibly the effect of oxygen at this altitude is to abolish the slight relative anoxemia which normally exists here. If this is the case one might observe a less marked response at sea level or even no response at all (8).…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been attributed to a local action of the anoxic mixture on the blood vessel walls resulting in a constriction of the pulmonary arterioles and pre-capillaries and an increase in pulmonary arterial pressure. Vagotomy and stellate ganglionectomy do not change the vascular response to the breathing of anoxic mixtures in the cat (1).The effect of breathing 100% oxygen on the pulmonary arterial pressure has been investigated in animals (1,3,4,8) but not adequately in man. Euler and Liljestrand (1) found that pure oxygen caused a fall in the pulmonary arterial pressure of cats which did not appear to these investigators to be the result of decreased blood flow, but rather to a dilatation of the pulmonary vasculature.…”
mentioning
confidence: 99%
See 1 more Smart Citation